2004
DOI: 10.1111/j.1365-2524.2004.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the process of diabetic care between south Asian and white patients in inner-city practices in Nottingham, UK

Abstract: The prevalence and complication rate of diabetes is higher amongst British south Asians when compared to the rest of the adult population. There is some evidence to suggest that there are differences in access to healthcare in the UK for different ethnic groups, but there has been little research examining differences in processes of care between ethnic groups and place of delivery of diabetic care. The present study was a retrospective, multi-practice audit exploring differences in the processes of diabetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…2002). There is further evidence that patients who report ethnic discrimination in their lives have a higher incidence of poor health (David & Kendrick 2004) and a far lower probability of receiving clinical monitoring tests (Ryan et al. 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2002). There is further evidence that patients who report ethnic discrimination in their lives have a higher incidence of poor health (David & Kendrick 2004) and a far lower probability of receiving clinical monitoring tests (Ryan et al. 2008).…”
Section: Resultsmentioning
confidence: 99%
“…2005) and community and primary care group drop– in sessions (Rhodes & Nocon 2003). There is also further scope for strengthening relationships between primary and secondary care (Hawthorne 1990, David & Kendrick 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The social and economic marginalisation of immigrants noted in the present Canadian study have been reported for other nations, notably the United Kingdom (Blakemore 2000). Recent reports reveal that health and social services for immigrants in the United Kingdom are less effective than those for non‐ethnic minorities, affecting access and use of available services (Blakemore 2000, Rhodes & Nocon 2003, David & Kendrick 2004, Quickfall 2004). In Canada, since the responsibility for immigrant settlement, health and social services is provincial, the disparities in services offered to immigrants vary.…”
Section: Discussionmentioning
confidence: 99%